Exploring the future energy-mobility nexus: The transportation energy & mobility pathway options (TEMPO) model. (September 2021) - Muratori, Matteo; Jadun, Paige; Bush, Brian; Hoehne, Chris; Vimmerstedt, Laura; Yip, Arthur; Gonder, Jeff; Winkler, Erin; Gearhart, Chris; Arent, Douglas
Highlights: Document the approaches and methods used in the TEMPO model. All-inclusive passenger and freight transport demand model that covers the entire U.S. Generate scenarios of technology adoption and future energy use and emissions. Innovative household-level representation of passenger mobility and choices. Comparison with the EIA AEO for a business-as-usual scenario. Abstract: This paper documents the approaches and methods used in the Transportation Energy & Mobility Pathway Options™ (TEMPO) model to evaluate passenger and freight demand for transportation and mobility services, project vehicle ownership and technology adoption decisions, and determine transport mode choices to derive scenarios of future energy use and emissions. TEMPO is an all-inclusive transportation demand model that covers the entire United States, with an implicit spatial resolution and an hourly temporal resolution that allows for generating time-resolved energy use profiles to assess multisectoral integration aspects. Key features of the TEMPO model include the ability to perform endogenous out-of-sample forecasting to extrapolate recent emerging trends and analyze impacts of disruptive technological breakthroughs and behavioral changes. TEMPO employs an innovative representation of passenger mobility demand stemming from household-level decisions that determine vehicle adoption, ownership, and use based on sociodemographics (e.g., income, household composition), technology attributes (e.g., travel cost, time), geography (e.g., urban, suburban, rural) and population-specific multiday mobility and travel requirements. This representation enables a more forward-looking perspective on the use of new mobility options and the adoption of alternative fuel vehicles, as well as a more accurate representation of their energy usage profiles than previous modeling approaches. A comparison with the U.S. Energy Information Administration's Annual Energy Outlook showcases the ability of TEMPO to accurately replicate widely accepted projections by representing the key elements of the entire transportation sector at the appropriate level of resolution. TEMPO is intended to generate future scenarios of technology adoption, energy use, and emissions in the transportation sector to compare alternatives, inform decision makers, and assess integration with energy infrastructure and supply systems at an appropriate spatiotemporal resolution.